The assessment of microfactory concept to manufacture new generation electric vehicles - Alptekin, Büşra (My University, 2020)
Bu tezin öncelikli amacı, sayıca az büyük otomotiv üreticilerinin tekelinde olan sektöreyeni bir üreticinin girmesine olanak saglayan alternatif bir üretim konsepti sunmaktır.Mikrofabrika konsepti ile içten yanmalı konvensiyonel araç üreticilerinin domine ettigisektörde yeni nesil, elektrikli konsept araçların üretimi için kobilere ve kendi yerli otomobiliniüretmek isteyen ülkelere rekabet edilebilir bir model saglanmaktadır. Literatürçalısması kapsamında local üretim, dagınık üretim sistemleri ve bunlara baglı olarakmikrofabrika teriminin literatürdeki karsılıkları analiz edilmistir. Bu tezde sunulan konseptteliteratürden farklı olarak elektrikli araç üretimi için yeni bir mikrofabrika yöntemitarif edilmistir. Son yıllarda, elektromobiliteyle birlikte artan yeni trendler ve bunlarınsagladıgı imkanlar öne çıkarılmıstır. Konvansiyonel teknikler ile yeni üretim paradigmasıarasındaki farkın ayrıntılı bir analizi yapılmıstır. Bu çalısmada, mikro-fabrika ilkeleri,yerlesim planından, operasyon asamalarına, mikrofabrikalar için paylasım ekonomisinedayanan tedarik zinciri yönetimden is planına kadar detaylı bir sekilde incelenmistir.Önerilen yöntem sürdürülebilirlik açısından da degerlendirilmistir. Özetle bu tez, mikrofabrikanın,akıllı imalat araçlarını kullanarak, düşük ölçekli yatırımla küçük ölçekli üretimdegüvenli, kitleselleşmeye uygun ve verimli şehir tipi elektrikli araçların üretimi içinsürdürülebilir bir üretim modeli sunduğunu göstermektedir.

The electromobility presents a potential for nations to develop and produce their domesticcars especially for emerging markets. This thesis proposes a new concept, calledmicrofactory, for manufacturing new generation Electric Vehicles (EV). It is a big challengefor newcomers to enter the automotive market as this industry remains heavilyunder the control of large OEMs. In this study, the current automotive industry, whichdepend on the conventional technologies and its drawbacks described. There are threemain de facto monopoly in the automotive industry are addressed; the first two of them,the required technology and knowledge to manufacture the Internal Combustion Engine(ICE) and the chassis, and the third one is the difficulty of reaching government funding.Therefore, the microfactory represents an alternative solution to overcome the existingmonopolies with the electric motor, a tubular chassis, and novel business model respectively.The new opportunities with electromobility trends and its potentials to create newecosystem is presented for countries who want to produce its domestic car. A detailedanalysis of the difference between conventional techniques and new production paradigmis also presented in in terms of sustainability dimensions and cost perspective. In particular,the principles of microfactory from the layout to the supply chain managementincluding the sharing economy are presented. This study indicates that the microfactoryis a sustainable production model for manufacturing of safe, secure customized and efficienturban electric vehicles using smart manufacturing tools in small-scale productionwith a low investment. The aim of this paper is to propose a new disruptive manufacturingmethod that allows a quicker entry for new players in automotive industry especiallyfor EVs.
Keywords: advanced manufacturing technology; akıllıüretim; electric vehicles; elektrikli araçlar; Endüstri mühendisliği; esnek üretim sistemleri; flexible manufacturing; Industrial engineering; microfactory; mikrofabrika yöntemi automotive industry; otomotiv üretimi; sustainable production; sürdürülebilir üretim